An experimental study of flow boiling in minichannels at high reduced pressure. (July 2017) - Belyaev, A.V.; Varava, A.N.; Dedov, A.V.; Komov, A.T.
Highlights: The main regimes of flow boiling were recorded for conditions that varied from highly subcooled flow to saturated flow and include data of dryout onset. The results for wall temperature and pressure drop depending on heat flux for various parameters are typical for subcooled flow boiling. Increases of pressure, when other flow parameters and heat flux are fixed, result in a significant reduction of pressure drop. A comparison between the experimental and calculated data for flow boiling heat transfer is presented. The method of calculation of flow boiling heat transfer in minichannels at high reduced pressure was developed. Division of regimes by boiling type is more appropriate than universal approaches. For high reduced pressure (pr > 0.4), qualitative differences from the results obtained in regular tubes in flow boiling and convection heat transfer characteristics in minichannels were not observed. Abstract: This paper presents an experimental setup and experimental data for heat transfer and pressure drops in flow boiling. Experimental study on hydrodynamics and heat transfer were performed for R113 and RC318 in two vertical channels with diameters of 1.36 and 0.95 mm and lengths of 200 and 100 mm, respectively. The inlet pressure-to-critical pressure ratio (reduced pressure) was pr  =  p / pcr  = 0.15–0.9, the mass flux ranges were between 770 and 4800 kg/(m 2  s), and inlet temperature varied from 30 to 180 °C. The primary regimes of flow boiling were obtained for conditions that varied from highly subcooled flows to saturated flows and include data for dryout onset. A comparison between the experimental and calculated data for pressure drops is presented. The influence of flow conditions (i.e., mass flow rate, pressure, inlet temperature, and the channel diameter) on the heat transfer coefficient and heat flux is presented in addition to a comparison between the experimental and calculated data for flow boiling heat transfer.